2020
DOI: 10.1371/journal.pone.0237051
|View full text |Cite
|
Sign up to set email alerts
|

What’s the temperature in tropical caves?

Abstract: Hourly temperature was measured for approximately one year at 17 stations in three caves in Quintana Roo, Mexico. Thirteen of these stations were in the extensive twilight zones of all three caves. All seventeen stations showed seasonality in temperature with a 3°C drop during the Nortes season. Two of the caves, Muévelo Sabrosito and Muévelo Rico, showed greater variability during the winter months while in Río Secreto (Tuch) variability was greatest during the rainy season. Río Secreto is less open to the su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…The retractions of forests in drier periods may have been responsible for the isolation of several lineages highly dependent on the humidity inside caves (Gnaspini, 1997). Deep subterranean habitats are characterized by pronounced environmental stability and thermal inertia -including tropical caves, although the climatic stability is seemingly less pronounced (Mejía-Ortíz et al, 2021). Subterranean habitats may thus have acted as 'climatic refuges' (Ledesma et al, 2020;Mammola, Piano, et al, 2019) for the survival and diversification of subterranean-adapted species.…”
Section: Brazilmentioning
confidence: 99%
“…The retractions of forests in drier periods may have been responsible for the isolation of several lineages highly dependent on the humidity inside caves (Gnaspini, 1997). Deep subterranean habitats are characterized by pronounced environmental stability and thermal inertia -including tropical caves, although the climatic stability is seemingly less pronounced (Mejía-Ortíz et al, 2021). Subterranean habitats may thus have acted as 'climatic refuges' (Ledesma et al, 2020;Mammola, Piano, et al, 2019) for the survival and diversification of subterranean-adapted species.…”
Section: Brazilmentioning
confidence: 99%
“…Even among the regions there are important differences in the diversity not only in the composition of genus or families, too in the number of species and in the specimens registered, by example due that the regions are big land extension is few possible that only one or two specimens were registered, is we check the numbers of index as Chao's or Burman & Overton the diversity estimated increase few because the taxa included in the analysis had a good representation in the area, someone are cosmopolitans in the same region. By another aspect is the subterranean environments that in first instance was classified in dry, semi-dry, freshwater flooded, and anchialine caves as has been reported in several opportunities [36], but in recently studies has been reported that even in the tropical dry caves there are some different according with the temperature and humidity that produce a major heterogeneity because these features are changing in relation with outside [37,38], and in semi-dry caves these features have a relation with the oxygen inputs in the subterranean aquatic habitats. In the Anchialine caves the size of freshwater lenses are the main changes to energy entrance and the environmental stability [28].…”
Section: Discussionmentioning
confidence: 99%
“…The open source base maps are from INEGI (Instituto Nacional de Estadistica y Geografia). From: Mejía-Ortíz et al [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Relative humidity (along with temperature, see Mejía-Ortíz et al [ 15 , 28 ]) was measured at hourly intervals for the following dates:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation